2017
DOI: 10.3892/etm.2017.5550
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of tight junction protein�occludin is associated with the protective effect of mosapride against aspirin‑induced gastric injury

Abstract: Abstract.Mosapride is known to affect gastric motility, however whether mosapride has anti-ulcergenic effects in gastric mucosal injury is unclear. The aim of the present study was to investigate the effects of mosapride on aspirin-induced gastric injuries. GES-1 cells were cultured and divided into 5 groups: Control group, aspirin injury group (treated with 18.2 mmol/l aspirin) and mosapride pretreatment groups (treated with 0.4, 0.5, or 0.6 µmol/l mosapride). Cell proliferation was evaluated via MTT assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It has also been reported that OCLN and ZO1 are not only capable of controlling paracellular macromolecule permeability but also interacting with intracellular signaling pathways that regulate and maintain intestinal epithelial permeability, subsequently enhancing intestinal epithelial barrier function [25][26][27][28][29]. To further understand the interaction between miR-144, OCLN/ZO1 and L. casei LC01 on regulating intestinal permeability in IECs, we transfected IECs with miR-144 and pcDNA3.1-OCLN/ZO1 under L. casei LC01 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that OCLN and ZO1 are not only capable of controlling paracellular macromolecule permeability but also interacting with intracellular signaling pathways that regulate and maintain intestinal epithelial permeability, subsequently enhancing intestinal epithelial barrier function [25][26][27][28][29]. To further understand the interaction between miR-144, OCLN/ZO1 and L. casei LC01 on regulating intestinal permeability in IECs, we transfected IECs with miR-144 and pcDNA3.1-OCLN/ZO1 under L. casei LC01 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin was shown to cause damage in the gastric system in a rat model by decreasing the plasma membrane protein of tight junctions, occludin expression, which was reversed by pretreatment with another drug mosapride. 17 High-dose of ibuprofen caused jejunal perforations even in short-courses. 18 Another anti-inflammatory drug, naproxen, causes gastric antral ulcerations, and an increase of lipid peroxide levels, but the effect was reversed with curcumin.…”
Section: Current Targets and Their Limitationsmentioning
confidence: 99%
“…Cells in the groups were treated with Codonopsis decoction subsequently cultured at 37˚C for 24 h. Following this, 10 µL of MTT solution (5 mg/mL; Sigma-Aldrich; Merck KGaA) was added to each well and incubated at 37 ˚C for 4 h. The culture medium was removed, dimethylsulfoxide (DMSO, Sigma-Aldrich; Merck KGaA) was added to each well and cells were incubated at 37˚C for 10 min, following which the absorbance (A) of MTT was measured at 490 nm using a microplate reader (Bio-Rad Laboratories, Inc., Hercules, CA, USA). According to the above test results: cells were subsequently divided into control group (1640 only), positive control group (3.3 mg/mL aspirin +10 mg/mL OME), aspirin injury group (3.3 mg/ mL) and Codonopsis decoction groups (3.3 mg/mL aspirin + 0.05, 0.1 and 0.2 mg/mL Codonopsis decoction) [14]. Cells in the groups were treated with aspirin or Codonopsis decoction subsequently cultured at 37˚C for 12 and 24 h. All experiments were repeated 3 times.…”
Section: Mtt Assaymentioning
confidence: 99%